Correlation between dental arch width and sagittal dento-skeletal morphology in untreated adults. - Atefe Saffar Shahroudi; Tahura Etezadi (Tehran University of Medical Sciences, 2013)
Dental arch form is one of the most important characteristics of dentition. However, this dimension usually receives less attention in diagnosis or treatment planning and orthodontic patients are traditionally classified with regard to their sagittal characteristics. The objectives of this study were to investigate if a relationship exists between the dental arch width (transverse dimension) and sagittal skeletal and dental parameters in orthodontic patients.Dental casts and lateral cephalograms of 108 consecutive untreated Iranian patients (47 males and 61 females) between 16 and 31 years of age were evaluated. Arch width (AW) parameters including upper and lower inter-molar width (UIMW and LIMW) and upper and lower inter-canine width (UICW and LICW) were measured by a digital caliper. Sagittal parameters included SNA and SNB angle and Wits' appraisal obtained from lateral cephalograms in addition to upper and lower arch length (UAL and LAL) obtained from dental casts. The correlation between the aforementioned parameters was evaluated applying Pearson correlation coefficients. Molar and canine relationship according to Angle's classification was also recorded and the means of all parameters were compared between three occlusal relationship classes and two gender groups by means of two-way ANOVA.According to statistical analysis a significant positive correlation between sagittal parameters and arch width measures exists between SNA and UICW and between LICW and LAL. Upper and lower ICW were significantly correlated, the relationship between upper and lower IMW and between UAL and LAL were significant. Among sagittal measures, both UAL and LAL were correlated with the ANB angle. The means of arch width parameters in three occlusal classes were not significantly different.The only significant correlation between arch width and sagittal parameters existed between UICW and SNA angle and between LICW and LAL. No significant difference of the arch width parameter was observed between the three occlusal classes.